Interest deductibility and thin capitalization rules after the Peruvian Income Tax Law and BEPS Action 4 - Botto Denegri, Francisco (2019)
Legislative Decree 1424 and Supreme Decree 338-2018-EF were aimed at modifying the Income Tax Law in matter of interest deductibility. The aforementioned Decrees have modified the thin capitalization rules by which companies established in Peru were regulated. Thereby, these adjustments seem to move the goalposts where foreign investment is concerned. In this article, the authors review the evolution of the thin capitalization framework in recent decades. Based on this concept, they analyze the rules in force until 2018 as well as those enacted between 2019 and 2020. Through this approach, they criticize the implementation of the BEPS Action 4 rules that will be applicable from 2021 since their effects will have economic repercussions both internally and externally.